Zastosowanie systemu szczelnej irygacji w czasie operacji zaćmy w zapobieganiu rozwojowi zmętnienia torebki tylnej - Kluś, Adam; Rękas, Marek; Rudowicz, Jacek; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The possibility of isolated use of pharmacological agents to selectively destroy anterior capsule epithelial cells and avoid toxic side effects on other tissues has become the aim of numerous research studies. Creation of a precise, tight, safe system which would allow delivery of pharmaceutical agents into the lens capsule following cataract extraction seems to be a solution. Thus, the aim of our study is to present a surgical technique preventing the development of posterior capsule opacification (PCO) after cataract surgery with the use of sealed-capsule irrigation system (SCI) – Perfect CapsuleTM device.